SOSIALISASI PERAN PERPUSTAKAAN DIGITAL DALAM PEMBELAJARAN JARAK JAUH PADA SISWA - Elly Agustina Julisawati; Hurnaningsih Hurnaningsih; Fivtatianti Hendajani; Agustina Nicke; Wigiyanti Wigiyanti; Kokoy Rokoyah; Sudjiran Sudjiran (Abdi Jurnal Publikasi, 2023)
Digital libraries have an important role in supporting distance learning. In this digital era, easy and fast access to electronic learning resources allows students to study material anytime and anywhere. The digital library also supports student research by providing access to scholarly journals and online databases. In addition, through collaboration and interaction features, students can interact with teachers and fellow students, expanding their social network in distance learning. The digital library also helps with monitoring and evaluating student performance, as well as developing important digital literacy skills. With roles and benefits that continue to grow, digital libraries are expected to become an important component in an increasingly connected future education. Â